2020
DOI: 10.3389/fendo.2020.545973
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Testosterone and Estradiol in Mediation of Acute Neuroendocrine and Electroencephalographic Effects of Sevoflurane During the Sensitive Period in Rats

Abstract: Testosterone (T), predominantly acting through its derivative 17b-estradiol (E2), regulates the brain's sexual differentiation in rodents during the perinatal sensitive period, which mirrors the window of vulnerability to the adverse effects of general anesthetics. The mechanisms of anesthesia's adverse effects are poorly understood. We investigated whether sevoflurane alters T and E2 levels and whether they contribute to sevoflurane's acute adverse effects in postnatal day 5 Sprague-Dawley rats. The rats unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 46 publications
(99 reference statements)
1
26
0
Order By: Relevance
“…Estradiol usually activates the nuclear receptors estrogen receptor α and β. Our study found that it is ERα but not ERβ that increases in the hypothalamus and that it is ERα antagonists that inhibit EEG epileptic activity induced by sevoflurane exposure 22 . However, early experiments have shown that it can also affect synaptic function acutely through non‐genomic effects, which are rapid effects caused by the activity of membrane‐associated estrogen receptors activated by selective receptor agonists 58,59 .…”
Section: The Role Of Neuroactive Steroids In Sex Differences In Devel...mentioning
confidence: 63%
See 2 more Smart Citations
“…Estradiol usually activates the nuclear receptors estrogen receptor α and β. Our study found that it is ERα but not ERβ that increases in the hypothalamus and that it is ERα antagonists that inhibit EEG epileptic activity induced by sevoflurane exposure 22 . However, early experiments have shown that it can also affect synaptic function acutely through non‐genomic effects, which are rapid effects caused by the activity of membrane‐associated estrogen receptors activated by selective receptor agonists 58,59 .…”
Section: The Role Of Neuroactive Steroids In Sex Differences In Devel...mentioning
confidence: 63%
“…Our team has been committed to the research of the anesthetic puberty neurotoxicity mechanism, including previous published results show that the rodents after receiving sevoflurane, males of testosterone and estradiol levels detected on the rise,and causing seizures that can be detected by electroencephalogram (EEG), concurrently, changes in stress‐like corticosterone secretion and key genes for brain development were also detected. The results suggest that sevoflurane increases estradiol (E2) levels throughout the body by increasing E2 levels in the brain 22 . Another study showed that exposure to the volatile anaesthetic sevoflurane resulted in increased estradiol levels in male mice, as well as neurodevelopmental abnormalities resulting in cognitive impairment by activating the GABAA receptor (GABAAR) signalling pathway, which were mitigated by preconditioning male mice with the estradiol synthesis inhibitor Formestane and the NKCC1 inhibitor Bumetanide 23 .…”
Section: Gender Differences In Anaesthetic Effect and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplements of testosterone increase Ar gene expression in human studies [72, 73]. These observations are interesting in the context of published evidence showing that exposure to sevoflurane increases testosterone levels in male animals [74, 75] and that a surge of testosterone takes place during germ cell and gonadal sex differentiation [70]. It is therefore possible that Ar and related nuclear hormone receptors are responsible for bookmarking regions responsible for sevoflurane induced epimutations.…”
Section: Resultsmentioning
confidence: 87%
“…A previous study showed that sevo in the early postnatal period can cause depolarization of the cell membrane and excitatory damage by acting on GABA A R at the postsynaptic membrane of nerve cells (Martynyuk et al 2017). A recent study showed that sevo caused a signi cant increase in NKCC1 expression in the rat hypothalamus at postnatal day 5, which was reversed by the GABA A R blocker, bicuculline (Bic) (Li et al 2020). However, GABA A R and NKCC1 have not been speci cally investigated in the mechanism of myelin development and neuronal injury.…”
Section: Introductionmentioning
confidence: 99%